2022
DOI: 10.3389/fnins.2022.739201
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of m6A Methyltransferase in the Hippocampus of Tyrobp–/– Mice and Implications for Learning and Memory Deficits

Abstract: Loss-of-function mutations in the gene that encodes TYRO protein kinase-binding protein (TYROBP) cause Nasu-Hakola disease, a heritable disease resembling Alzheimer’s disease (AD). Methylation of N6 methyl-adenosine (m6A) in mRNA plays essential roles in learning and memory. Aberrant m6A methylation has been detected in AD patients and animal models. In the present study, Tyrobp–/– mice showed learning and memory deficits in the Morris water maze, which worsened with age. Tyrobp–/– mice also showed elevated le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…The Hippocampus_L and Hippocampus_R found in the AD-HC and EMCI-HC groups were reported as the pathogenic regions of AD. Chik et al ( Yuan et al, 2022 ) found that the neurosteroids in the hippocampus were changed during the progression of Lv et al (2022) found that compared to the healthy mouse, the mice having TYRO protein kinase-binding protein had insufficient learning and memory abilities, and the amyloid β in the hippocampus was increased, which worsened with aging. Liu et al (2022) proved that memory could be improved by enhancing the functional activity in the hippocampus and the medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippocampus_L and Hippocampus_R found in the AD-HC and EMCI-HC groups were reported as the pathogenic regions of AD. Chik et al ( Yuan et al, 2022 ) found that the neurosteroids in the hippocampus were changed during the progression of Lv et al (2022) found that compared to the healthy mouse, the mice having TYRO protein kinase-binding protein had insufficient learning and memory abilities, and the amyloid β in the hippocampus was increased, which worsened with aging. Liu et al (2022) proved that memory could be improved by enhancing the functional activity in the hippocampus and the medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent investigation has shown m 6 A methylated RNA and its protein partner heterogeneous nuclear ribonucleoprotein A2/B1 (HNRPA2B1) bind hyperphosphorylated tau and accumulate in neurofibrillary tangles as AD pathology worsens (Jiang et al, 2021). Recently, other studies have started to show an alteration in the levels of other epitranscriptomics regulators such as METTL3 with an effect on tau protein homeostasis in the brain (Lv et al, 2022; Tang et al, 2023) (Table 2).…”
Section: Altered Epiregulatory Mechanisms In Tauopathiesmentioning
confidence: 99%
“…The cDNA was diluted two-fold in RNAase-free ddH 2 O, then used as template (1 µL) in qRT-PCR with the ChamQ™ Universal SYBR qPCR Master Mix (cat# Q711-02, Vazyme, Nanjing, Jiangsu, China) and primers designed using the online tool https://www.ncbi.nlm.nih.gov/tools/primer-blast/ (Supplementary Table 4). The 2 −ΔΔCt method was used to measure mRNA levels relative to GAPDH [33]. Only genes with transcript Ct ≤ 30 were considered to be expressed.…”
Section: Rna Isolation and Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%